Self's murder - Schlink, Bernhard, 1944- (A Gerhard Self mystery, 2010)
Gerhard Self, the seventy-something, sambuca-drinking, Sweet-Afton smoking sleuth returns in a riveting new mystery about money-laundering, murder, and mafiosi. Despite his failing health and his girlfriend's pleading, Gerhard Self won't stop doing what he does best--investigating. And his most recent case is one of the most intriguing of his career. Herr Welker desperately wants to write a history of his bank, but to do so he needs Self to track down a mysterious silent partner. Self takes the job, but is soon accosted by a man who frantically hands him a suitcase full of cash and speeds off in a car, only to crash into a tree, dying instantly. Perplexed, and convinced there is more to the case than he is being told, Self follows the money. Soon he finds himself traveling to eastern Germany, where he encounters some of the most unsavory villains he has met yet.